Exclusive breastfeeding and maternal employment as determinants of toddler nutritional status in Banda Aceh, Indonesia - Burhanuddin Syam; Evi Dewi Yani; Rahmayani Rahmayani; Ismail Ismail; Nisrina Hanum; Munalita Munalita (AcTion: Aceh Nutrition Journal, 2026)
Child malnutrition remains a significant public health concern with long-term consequences for growth, cognitive development and morbidity. This study aimed to examine the association between exclusive breastfeeding, maternal employment, and nutritional status of toddlers in the Lampaseh Health Center area of Banda Aceh. A cross-sectional study was conducted on 47 mothers selected through random sampling. Data were collected using structured questionnaires and verified using health records. Nutritional status was assessed using the weight-for-age (WAZ) indicator, based on WHO standards. Data were analyzed using chi-square tests and odds ratios (OR). The results showed that children of employed mothers were more likely to be undernourished than those of unemployed mothers (OR = 5.25; p = 0.029). Similarly, toddlers who were not exclusively breastfed had a higher likelihood of undernutrition than those who were exclusively breastfed (OR = 10.77; p = 0.001). In conclusion, exclusive breastfeeding and maternal employment are significant determinants of the nutritional status of toddlers. However, the cross-sectional design and small sample size limit the causal inference and generalizability of the results. Strengthening breastfeeding support and targeted interventions for working mothers is recommended to improve child nutrition outcomes.